Wind to Select the Recreation Flying Site - Falavarjani, Nooshin Ghasemi (International Journal of Geography and Geology, 2015)
Soaring is a recreational activity and competitive sport where individuals fly unpowered aircraft known as paragliders. Also soaring Pilots need to understand the sky to fly successfully and safely. Wind can be re-evaluated in the growth of soaring. This paper provides wind as an integral part of paragliding for: Beginner pilots, Regular pilots, Good pilots. In this research Surfer and GIS software (IDW Method) used in evaluation of prevailing Wind speed and direction to create maps to select recreation flying site in Esfahan, Iran. The results revealed that, the most area and prevailing wind speed frequent is appropriate to the Regular pilot class.